(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
Employee performance is a very important factor for the continuity of a company’s business which can be influenced by motivation and interpersonal communication. The purpose of this study was to determine the effect of motivation and interpersonal communication on employee performance either partially or simultaneously. This research was conducted at PT. Kharisma Perkasa Dewata in Denpasar City with a population of 42 people who are company employees using census techniques. Data collection was carried out using observation, documentation, interviews, and questionnaires using a Likert scale. Based on the results of the analysis, it can be concluded that motivation and interpersonal communication have a positive and significant effect on employee performance partially and simultaneously